Evaluating the effectiveness of whatsapp to develop efl vocabulary for speaking performance - Raja Muhammad, Ishtiaq Khan (2021)
Vocabulary learning is an imperative part of learning language and it has a key role in speaking skill. The present study attempts to investigate how vocabulary learning through WhatsApp enhances learners’ speaking performance. It scrutinises the efficacy of WhatsApp application in developing EFL learners’ vocabulary and speaking performance of Saudi EFL learners. It also explores the attitudes of EFL learners on using WhatsApp application for vocabulary learning. The research links Mobile Learning (M-Learning) assisted vocabulary learning to speaking proficiency by looking at how to manage input for vocabulary development. The theoretical perspectives include Krashen (1989) Input Hypothesis and Cognitive Theories of Multimedia Learning (Mayer, 2009). The study employed a mixed method approach with a pre-test, post-test quasi-experimental design as the main data gathering method. The Productive Vocabulary Knowledge Test (PVKT) by Laufer and Nation (1999) and a speaking test were used to collect the quantitative data. Learner attitude questionnaires and semi-structured interviews were used to triangulate the findings of the research. The participants of the study were 60 EFL learners of Preparatory Year Program (PYP) of a public university in Saudi Arabia. Two preformed intact groups from the elementary level were randomly assigned into control and experimental groups. As for the analysis of the data, a statistical package for social sciences (SPSS) was employed for the quantitative analysis whereas the interview was subjected to thematic analysis. The findings of the research showed that the students in the experimental group performed better in both vocabulary and speaking tests. The outcomes of the questionnaire and the interview investigation also supported the efficacy of WhatsApp application as the analysis of the speaking and vocabulary tests. Differences in the mean scores of the pre-test and post-test of both groups showed that students who used WhatsApp application performed better in both speaking and vocabulary tests than the learners who did not. The results illustrated that the WhatsApp integration is favourable among learners in utilising visual learning materials. The findings of the study are useful for EFL students, teachers, researcher and curriculum designers to develop vocabulary for speaking proficiency by the implementation of M-learning. On the basis of the findings, the study endorsed WhatsApp application as a useful teaching tool in language learning.